Measuring students' exposure to temperature and relative humidity in various indoor environments and across seasons using personal air monitors - Ryan, Ian; Deng, Xinlei; Thurston, George; Khwaja, Haider; Romeiko, Xiaobo; Zhang, Wangjian; Marks, Tia; Yu, Fangqun; Lin, Shao (Hygiene and Environmental Health Advances (Online), 2022)
•Children are exposed to a wide range of thermal conditions throughout the day.•In New York State, exposures vary significantly by microenvironment and season.•Excess heat negatively affects academic performance and child health.•No indoor temperature standards exist for schools and homes.•Classrooms are too hot and dry during the majority of the school year. Background: Thermal comfort is essential for human well-being. Consistent exposure to uncomfortable thermal conditions indoors leads to reduced academic performance and adverse health outcomes in schoolchildren. In addition, children are more sensitive to thermal conditions due to physiological differences, yet their exposure to thermal conditions has not been adequately measured. Methods: This cross-sectional study evaluated students' exposure to temperature and relative humidity (RH) using personal air monitors. In this study, we recruited 90 students from 13 classrooms – 60 from 11 NYS primary school classrooms and 30 from two State University of New York at Albany classrooms. Each participant wore an AirBeam air monitor for 48 hours, and their data was transmitted to a cell phone provided by the researchers. Results: Primary school students were routinely exposed to temperatures exceeding ASHRAE standards (winter: 75⁰F, summer: 80.5⁰F), particularly in school in the spring (max=102⁰F, median=82⁰F). At home, temperatures exceeded standards in the evening around dinnertime. However, primary students were routinely exposed to RH below recommended standards in classrooms during all seasons (median=29%). However, the RH was significantly lower in the winter than in any other season (median=17%). Finally, university students were exposed to slightly higher temperatures and significantly lower RH than primary schoolchildren in the spring. Conclusion: These results suggest that students are exposed to uncomfortable thermal conditions, particularly in classrooms when attending class. Teachers should therefore be given more control over classroom ventilation and thermal conditions, while indoor temperature standards should be adjusted for school children. [Display omitted]